2019
DOI: 10.1101/576918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prenatal diagnosis of HNF1B-associated renal cysts: Need to differentiate intragenic variants from 17q12 microdeletion syndrome?

Abstract: Objective Large deletions of chromosome 17q12 (17q12DS) or intragenic variants in HNF1B are associated with variable developmental, endocrine and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe pre-and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to previous studies. MethodsPrenatal sequencing and postnatal chromosomal microarray analysis was performed in seven individuals with renal and/or neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Differences in deletion size (or other genetic modifiers) may also account for part of the observed phenotypic variation, although almost identical deletions (including in twins) may lead to variable phenotypes.The third patient had ASD as a main feature, in association with mild developmental delay, dysmorphic features and prenatal hydronephrosis. ASD has been previously reported in patients with 17q12 deletion, e.g.,Vasileiou et al [2019] [27] described 2 cases and Loirat et al (2010)[23] reported 3 unrelated boys with de novo 17q12 deletion, with ASD and kidney problems, hypothesizing that autistic behavior may be due to HNF1B deletion. Yet,Clissold et al (2016)…”
mentioning
confidence: 99%
“…Differences in deletion size (or other genetic modifiers) may also account for part of the observed phenotypic variation, although almost identical deletions (including in twins) may lead to variable phenotypes.The third patient had ASD as a main feature, in association with mild developmental delay, dysmorphic features and prenatal hydronephrosis. ASD has been previously reported in patients with 17q12 deletion, e.g.,Vasileiou et al [2019] [27] described 2 cases and Loirat et al (2010)[23] reported 3 unrelated boys with de novo 17q12 deletion, with ASD and kidney problems, hypothesizing that autistic behavior may be due to HNF1B deletion. Yet,Clissold et al (2016)…”
mentioning
confidence: 99%